Storytelling in design : defining, designing, and selling multidevice products / Anna Dahlström. - Dahlström, Anna (UX designer) (O'Reilly Media, Inc., 2019)
The number of devices we use on a daily basis is growing, with different devices playing different role at different times. Our ability as designers to control where users are coming from and how they get around the experiences we design is fading. Yet our need to ensure we understand where they are in their journey, so that we can deliver the right content and interactions at the right time and on the right device, is ever more important. By examining tried-and-tested storytelling principles from film, fiction, and music and applying them to the context of design and business, this book takes you on a journey to explore why storytelling matters and how you can apply it to your multi-device design projects and to your organisation.